Deep Versus Shallow PTAs : Rules Affecting Competition Dynamics–Antitrust, Competitive Neutrality, and Pro-Competition Economic Regulation - Martinez Licetti, Martha (World Bank, Washington, DC, 2020)
Even though many countries have opened to trade, markets in developing economies oftenunderperform due to anticompetitive behavior and restrictive regulatory frameworks by a fewdominant players. Effective competition policies offer a tool to complement and support governments’ efforts to reduce barriers to trade. Active competition among market players has the potential to mitigate vested interests and facilitate the opening of markets to trade and investment. Greater competition within national markets reinforces international competitiveness of potential exporters through increased incentives to foster productivity, innovation and efficiency. Additionally, international trade reinforces competition in national markets by increasing contestability, entry and rivalry through increased presence of foreign products, services and investments. Empirical evidence suggests, for example, that: (i) the elimination of entry barriers, increased rivalry and leveling the playing field in upstream sectors contribute to export competitiveness in downstream manufacturing sectors; (ii) pro-competition market regulation that reduces restrictions and promotes competition is an important determinant for trade; (iii) competition law enforcement can be traced to export performance and is complementary to trade reforms; and (iv) industries with more intense domestic competition will export more.